Health-related quality of life after laparoscopic repair of giant paraesophageal hernia: how does recurrence in CT scan compare to clinical success? - Henriikka Hietaniemi; Ilkka Ilonen; Tommi Järvinen; Juha Kauppi; Saana Andersson; Harri Sintonen; Jari Räsänen (BMC Surgery, 2020)
Abstract Background Computed tomography (CT) is widely used in the diagnosis of giant paraesophageal hernias (GPEH) but has not been utilised systematically for follow-up. We performed a cross-sectional observational study to assess mid-term outcomes of elective laparoscopic GPEH repair. The primary objective of the study was to evaluate the radiological hernia recurrence rate by CT and to determine its association with current symptoms and quality of life. Methods All non-emergent laparoscopic GPEH repairs between 2010 to 2015 were identified from hospital medical records. Each patient was offered non-contrast CT and sent questionnaires for disease-specific symptoms and health-related quality of life. Results The inclusion criteria were met by 165 patients (74% female, mean age 67 years). Total recurrence rate was 29.3%. Major recurrent hernia (> 5 cm) was revealed by CT in 4 patients (4.3%). Radiological findings did not correlate with symptom-related quality of life. Perioperative mortality occurred in 1 patient (0.6%). Complications were reported in 27 patients (16.4%). Conclusions Successful laparoscopic repair of GPEH requires both expertise and experience. It appears to lead to effective symptom relief with high patient satisfaction. However, small radiological recurrences are common but do not affect postoperative symptom-related patient wellbeing.